Organización contable en el Taller de Equipo Caminero “TRACTO SERVO” de la ciudad de Loja, periodo de octubre a diciembre del 2022. - Cueva Capa, Nathaly Jhuliana (2024)
The Curricular Integration Project titled "ACCOUNTING ORGANIZATION IN THE 'TRACTO SERVO' AUTOMOTIVE REPAIR SHOP IN LOJA CITY, FROM OCTOBER TO DECEMBER 2022," is developed taking into consideration the need for the shop to collect, organize and record transactions, and thus to determine the economic-financial situation of the company, facilitating appropriate decision-making by the owner for the management and achievement of the objectives for which the shop is created. Through the implementation of the accounting system, it was possible to accomplish the general objective, which is to implement the accounting system in the "TRACTO SERVO" automotive repair shop. In order to achieve the specific objectives outlined, an analysis of the economic activities of the company is conducted to elaborate a codified and ordered chart of accounts according to the needs and nature of the company. Additionally, a manual is created to detail the transactions and balances of each account category, including assets, liabilities, equity, revenues, costs, and expenses. Therefore, this manual is designed to provide guidance on proper record keeping throughout the implementation of the accounting process. Auxiliary records are designed for purchases, sales, accounts receivable, payment roles and accrual roles, which allow transactions to be correctly recorded in the journal. The process is carried out with the Initial Inventory, which includes the assets, rights, and obligations of the automotive car shop, as reflected in the Opening Balance Sheet. Transactions are recorded in the Journal on the basis of source documents. The multi-account or periodic inventory system is used, which facilitates the proper control of goods to determine the gross profit from sales. The General Ledger; Trial Balance; Accounting Worksheet with the adjustments. Finally, the Financial Statements are drawn up, with their respective explanatory notes. Several methods are used to carry out this research project: Scientific, Deductive, Inductive, Analytical, Synthetic, Mathematical and Statistical, which allowed the development of the study, facilitating the analysis of bibliographic sources and source documentation to record and collect the results.